Sociodemographic and socioeconomic inequalities in physical activity among Slovenian youth - Kirbiš, Andrej (Obzornik zdravstvene nege, 2014)
Introduction: Frequent physical activity has previously been found associated with numerous health benefits, yet it is unequally distributed across social strata, including in Slovenia. The aim of the present study was to examine the frequency of and inequalities in physical activity among Slovenian youth. Methods: A representative cross-sectional study of 907 men and women aged 16-27 years (xage = 21.90, s = 3.25, 48.3 % women) living in Slovenia was carried out examining the determinants of physical activity (measured with a single item on the frequency of physical activity in previous 7 days). Results: More than four out of ten young people (41.3 %) reported being vigorously physically active for at least 20 minutes daily only on two days or less in the previous week. Regression analysis indicated that eight predictor variables explained 4.2 % of the variance (Adjusted R2 = 3.4 %) in physical activity. Male gender was the only significant predictor of more frequent physical activity (ß = 0.20, p < 0.001). In addition, interaction effect was detected with gender moderating the association between age and physical activity (ß = -0.10, p < 0.05). Discussion and conclusion: Socioeconomic gradient in physical activity was not detected. Future studies should examine additional indicators of socioeconomic status and deprivation. The study results could provide a basis for programmes and interventions on physical activity that should target especially young women.
Keywords: communication medium; dobro počutje; gibanje; health; lifestyle; media; mediji; physical activity; socioeconomic inequalities; socioekonomske neenakosti; well-being; zdravje; življenjski slog